Evaluating the economic effect of sustainable agricultural practices on small-scale farmers in the Eastern Cape Province: a propensity score matching analysis - Lelethu Mdoda; Olwethu Loki; Misery M. Sikwela (International Journal of Agricultural Sustainability)
Agricultural productivity in sub-Saharan Africa is low, worsened by the COVID-19 pandemic and climate change. Sustainable Agricultural Practices (SAPs) offer pathways to improve productivity and resilience. This study assessed the impact of SAPs on the farm income of small-scale farmers in Eastern Cape Province. Using a cross-sectional research design and multistage sampling, data were collected from 168 smallholder farmers through semi-structured questionnaires. Descriptive statistics, binary logistic regression, and propensity score matching were used for analysis. Results showed that 70% of farmers were female, averaging 45, and six household members worked as family labour. The study found that 64% of farmers who adopted SAPs had improved farm returns. Empirical results revealed that adopting all five SAPs positively impacted farm income more than adopting one or two. The study concludes that SAPs enhance farmers' welfare and livelihood. Based on the results, the study recommends a gradual transition to these practices, restoring soil health, controlling weeds, reducing erosion, and aligning with the UN's Sustainable Development Goals.